Country Partnership Framework for Ukraine for the Period FY17-21 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
The Country Partnership Framework (CPF) for Ukraine covers the 5 years from FY17 to FY21. The CPF is aligned with the objectives of the country’s development strategy as outlined in the Government Program and Action Plan adopted in April 2017 and is based on the findings and recommendations of the World Bank Group (WBG) Systematic Country Diagnostic (SCD) for Ukraine. The objective of the WBG CPF in Ukraine during FY17-FY21 is to promote sustained and inclusive economic recovery after nearly a decade of stagnation and two years of economic crisis. The focus areas of the CPF broadly parallel the pathways identified in the SCD, but are further prioritized. The engagement will be highly selective and based on the intersection of the Government’s development agenda, the development challenges and approaches outlined in the SCD, and the comparative advantage and capacity of WBG to deliver. The resulting CPF focus areas are : (i) Better Governance, Anticorruption, and Citizen Engagement; (ii) Making Markets Work; (iii) Fiscal and Financial Sustainability; and (iv) Efficient, Effective, and Inclusive Service Delivery.